A documentação patrimonial: gênese e fluxo dos processos de tombamento do Museu Prudente de Moraes - Grigoleto, Maira Cristina [UNESP] (2009)
The present work comes from an initial inquiry about the materialization of the information. With the intention of developing this idea, in the specific case of the necessary information for transforming a good into a patrimony, we present a general discussion about the definition of the patrimony and the institutions that legalize it. In a second moment, we focate our observation on an interpretation of the document, in this case, of the document as thing. Made these considerations we start to analyze a specific architectural good: President Prudente de Moraes‟ house located in the city of Piracicaba/SP. For this analysis, we understand that it should be considered the construction of the character's image, as well as the description of the space to which it was linked. Finally, we compare the patrimonial processes done by three preservationist instances: IPHAN, CONDEPHAAT and CODEPAC. The intention of this comparison was to evidence what form has the document that, considered as a space of power forms and of materialization of values, it determines the own patrimony, and not the opposite, as commonly is thought.